2016
DOI: 10.1016/j.ememar.2016.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Institutions and corporate capital structure in the MENA region

Abstract: This paper provides novel evidence on firmand country-level determinants of firm capital structure decisions in the MENA region. Using a sample of 444 listed firms from ten countries, over the 2003-2011 period, we find that MENA firms have target leverage ratios towards which they adjust over time. Yet, the speed of adjustment varies from one country to another. Our findings also suggest that some firm-level factors are associated with leverage consistent with the trade-off and pecking order theories of capita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
136
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 109 publications
(157 citation statements)
references
References 74 publications
19
136
2
Order By: Relevance
“…Only a few studies mentioned the macroeconomic factors which affected the capital structure of corporations in Vietnam, typically the study by Dang Thi Quynh Anh and Quach Thi Hai Yen (2014), Vo Thi Thuy Anh et al (2014). It is worth mentioning that the identification of influencing elements in these studies was based on static capital structure; whereas several recent findings from Yang et al (2015), Temimi et al (2016), Belkhir et al (2016) showed that the dynamic capital structure would be more appropriate when considering the impact of macro factors on the capital structure of firms. Besides, these papers tilted in favour of macroeconomy and financial development, and no studies have addressed the affectation of institutional quality on capital structure decisions of Vietnamese firms.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Only a few studies mentioned the macroeconomic factors which affected the capital structure of corporations in Vietnam, typically the study by Dang Thi Quynh Anh and Quach Thi Hai Yen (2014), Vo Thi Thuy Anh et al (2014). It is worth mentioning that the identification of influencing elements in these studies was based on static capital structure; whereas several recent findings from Yang et al (2015), Temimi et al (2016), Belkhir et al (2016) showed that the dynamic capital structure would be more appropriate when considering the impact of macro factors on the capital structure of firms. Besides, these papers tilted in favour of macroeconomy and financial development, and no studies have addressed the affectation of institutional quality on capital structure decisions of Vietnamese firms.…”
Section: Introductionmentioning
confidence: 99%
“…In general, most of the researches explored that those aspects included not only the factors that reflected companies' characteristics such as size, profitability, growth opportunities, tangible assets, solvency, bankruptcy risk, etc. (Titman and Wessels, 1988;Rajan and Zingales, 1995;Wald, 1999;Michaelas et al, 1999;Booth et al, 2001;Deesomsak et al, 2004;Jong et al, 2007;Chakraborty, 2010;Handoo and Sharma, 2014) but also macroeconomic conditions (such as corporate income tax rates, inflation rates, economic growth and interest rates (Booth et al, 2001;Deesomsak et al, 2004;Bokpin, 2009;Bostos et al, 2009;Frank and Goyal, 2009;Mokhova and Zinecker, 2014;Memon et al, 2015;Temimi et al, 2016;Belkhir et al, 2016)), as well as financial development (Booth et al, 2001;Deesomsak et al, 2004;Bokpin, 2009;Kayo and Kimura, 2011;Temimi et al, 2016;Belkhir et al, 2016), and institutional quality (Mokhova and Zinecker, 2014;Belkhir et al, 2016) of the host countries, where the companies were operating.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations